Introducing Hajj Values to Early Childhood Through Experiential Learning at the Sudiang Ka’bah Replica - Hasyim; Ramlan; Safitri, Dian; Fitrizki, St Dewi Nurul; Nurhikmah; Elysa, Ratianarimamy Niriko (Jurnal Al Burhan, 2025)
Developing children's religious character begins with introducing them to Hajj values at a young age. This article focuses at an interactive outing class session that TK Wulil Amri planned at the Replika Ka'bah Sudiang to teach the fundamentals of Hajj customs. Children engage in simplified Hajj traditions including Tawaf, Sa'i, and Arafah during this activity. The findings demonstrate that the approach effectively raises kids' interest in studying religious principles. It also strengthens their understanding of unity, discipline, and obedience in a way that suits their developmental stage. This study provides concrete evidence of how experiential learning can make Islamic education more engaging and meaningful. By focusing on enjoyable and practical methods, this article contributes to innovations in Islamic education, especially in creating effective strategies for early childhood learning. For future research, this approach can be expanded to other educational levels, such as primary or secondary schools, to investigate its efficacy at various developmental stages. Comparative research could also be done to investigate the influence of manasik haji simulations in various cultural or socioeconomic circumstances.